2012
DOI: 10.1097/mcg.0b013e3182371285
|View full text |Cite
|
Sign up to set email alerts
|

High HBV-DNA Titer in Surrounding Liver Rather Than in Hepatocellular Carcinoma Tissue Predisposes to Recurrence After Curative Surgical Resection

Abstract: In patients with HBV-associated HCC, high HBV-DNA titer in surrounding liver rather than in the HCC itself is associated with posthepatectomy HCC recurrence after curative surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Chronic hepatitis B virus (HBV) infection results in liver fibrosis/cirrhosis and development of hepatocellular carcinoma (HCC) [1], [2]. Establishment of chronic HBV infection is inversely associated with patient's age with neonatal and infants most susceptible, while adults are mostly resistant to chronic infection [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis B virus (HBV) infection results in liver fibrosis/cirrhosis and development of hepatocellular carcinoma (HCC) [1], [2]. Establishment of chronic HBV infection is inversely associated with patient's age with neonatal and infants most susceptible, while adults are mostly resistant to chronic infection [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…The second stage was an RCT carried out to validate the findings. Of these studies, nine were conducted in Mainland China [12,18,21,22,24,26,29,31,32], four in Taiwan [19,23,28,30], three in Korea [6,20,25], two in Hong Kong [5,13], and one in Japan There was significant heterogeneity between the studies regarding recurrence (I 2 = 69 %; P = 0.02), but not between the studies regarding DFS and OS (Fig. 1).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…This is consistent with a randomized clinical trial that showed that nucleotide/nucleoside analog treatments decreased HBV-HCC recurrence [ 10 ]. Some studies indicated that serum HBV DNA status is a more sensitive criterion compared with HBV DNA titre in liver tissues [ 8 , 11–15 ]. In this current study, we refer to serum HBV DNA.…”
Section: Discussionmentioning
confidence: 99%